Potret Kemiskinan dalam Puisi Orang-Orang Miskin Karya W.S Rendra dan Lirik Lagu Pinggiran Kota Besar Karya Iwan Fals - Nabiilah Chaermy Nanda (Jurnal Syntax Admiration, 2024)
Poverty is a problem that has not been resolved until now. this study will discuss the portrait of proverty in a literary work, namely a poem by W.S Rendra entitled Orang-Orang Miskin and the lyrics of Iwan Fals’ song entitled Pinggiran Kota Besar. The type of research applied is descriptive qualitative research using comparative literature as a method. The approach used in this research is an objective approach. This research was conducted to see the form of proverty described in poetry Orang-Orang Miskin by W.S Rendra and song lyrics Pinggiran Kota Besar by Iwan Fals. The results found in this research are similarities and differences in showing poverty in poetry and song lyrics. The similarities found are in the form of topics discussed, namely regarding poverty and criticism of the government regarding justice while the things that distinguish the way poverty is described.